A Systemic Functional Linguistics Analysis of Suicide Notes in Indonesia - Bernard Nainggolan; Reli Handayani; Uswatun Hasanah; Rosinta Norawati (Global Expert: Jurnal Bahasa dan Sastra, 2026)
This study explores Indonesian suicide notes informed by Systemic Functional Linguistics (SFL) to analyze how final experiences are linguistically constructed. Drawing on a corpus of 11 Indonesian suicide notes (containing 130 clauses) compiled from digital news archives between 2023 and 2025, the research analyzed how grammar functions ideationally, interpersonally, and textually. The findings show that Relational processes (38.3%) and Mental processes (20.0%) dominate the texts. This proves that the notes focus heavily on internal feelings and self-definition rather than external actions. In contrast, Material processes make up 25.0% of the data and shift behavior based on the recipient, acting as practical task instructions. Interpersonally, the notes rely on a mix of Declarative statements (74.6%) and Imperative commands (19.2%) to pass emotional and practical duties onto survivors. Textually, the heavy use of first-person pronouns as the sentence-starting Topical Theme (74.8%) keeps the author at the center and forces the reader to see the tragedy entirely through their eyes. This study demonstrates that these notes operate as complex tools for meaning-making rather than simple emotional outbursts. Finally, the paper concludes by detailing how these results contribute practically to forensic linguistics for text verification and to psychological counseling for spotting critical language warning signs of deep mental distress. Keywords: Mood analysis, suicide notes, systemic functional linguistics, textual theme transitivity